BRIDGING A GAP IN THE GREATER SUNDA: FIRST RECORD OF YELLOW-BREASTED FLOWERPECKER PRIONOCHILUS MACULATUS IN BANGKA ISLAND, SUMATRA - Iqbal, Muhammad (Unmuh Babel Press, 2025)
The Yellow-breasted Flowerpecker Prionochilus maculatus is a species of flowerpecker found in Southeast Asia, Sumatra and Kalimantan. This species has never been recorded in Bangka Island, Sumatra. On June 4 2022, this species was documented in Kemuja Village (02°05'07